Outcomes of RDAVR with Coronary Revascularization: 3-year Results from the German INCA Registry - Lenos, Aristidis; Strauch, Justus T.; Schlömicher, Markus; Fleissner, Felix; Valencia-Nunez, Diana M.; Garbade, Jens; Gottardi, Roman; Massoudy, Parwis; Kamler, Markus; Malik, Rizwan; Wimmer-Greinecker, Gerhard; Walther, Thomas; Gummert, Jan; Bramlage, Peter; Diegeler, Anno (The Thoracic and Cardiovascular Surgeon, 2025)
Background The long-term outcomes of combined rapid-deployment aortic valve replacement (RDAVR) with coronary artery bypass graft surgery (CABG) are not well explored. We report 3-year results from the INCA registry on combined RDAVR with CABG.Methods INCA is a prospective, multicenter registry that enrolled 224 patients undergoing RDAVR with CABG at 10 cardiac institutions in Germany. Prosthetic valve hemodynamics, clinical outcomes, and quality of life (QoL) up to 3 years were assessed.Results The mean age of patients was 73.6 ± 6.1 years, and the mean logistic EuroSCORE was 7.8 ± 6.0%. The mean number of distal arterial and venous anastomoses was 3.13 ± 1.56, aortic cross-clamp time was 79.4 ± 24.1 minutes, cardiopulmonary bypass time was 109.6 ± 34.5 minutes, and operation time was 224.2 ± 62.7 minutes. The majority of implanted valve size was 25 mm. At baseline, 11 patients (4.9.%) had a permanent pacemaker. Postoperatively, 17 patients (7.6%) required a new pacemaker implantation (5.4% valve-related). All-cause mortality at 30 days was 2.2%, and 11.2% at 3 years. Patient QoL (SF-12v2) was significantly restored and maintained for up to 3 years (p < 0.001). Five patients (0.9%) underwent reoperation related to endocarditis. The postimplant mean gradient was 9.2 ± 3.7 at discharge and 8.9 ± 4.6 mm Hg at 3 years.Conclusion Combined RDAVR with CABG procedure is safe and effective over time. It offers stable and low transvalvular gradients with satisfactory clinical outcomes at 3 years. The pacemaker rate appears to be slightly increased, with no significant clinical effect at 3 years.
Keywords: rapid-deployment aortic valve replacement; structural valve degeneration; valve durability